Cost effectiveness of bronchial thermoplasty in patients with severe uncontrolled asthma*. (7th February 2016) - Zein, Joe G.; Menegay, Michelle C.; Singer, Mendel E.; Erzurum, Serpil C.; Gildea, Thomas R.; Cicenia, Joseph C.; Khatri, Sumita; Castro, Mario; Udeh, Belinda L.
Abstract: Rationale : Based on its clinical effectiveness, bronchial thermoplasty (BT) was approved by the Food and Drug Administration in 2010 for the treatment of severe persistent asthma in patients 18 years and older whose asthma is not well-controlled with inhaled corticosteroids and long-acting beta-agonist medicines. Objective : Assess the 10 year cost-effectiveness of BT for individuals with severe uncontrolled asthma. Methods : Using a Markov decision analytic model, the cost-effectiveness of BT was estimated. The patient population involved a hypothetical cohort of 41-year-old patients comparing BT to usual care over a 10-year time frame. The main outcome measure was cost in 2013 dollars per additional quality adjusted life year (QALY). Results : Treatment with BT resulted in 6.40 QALYs and $7512 in cost compared to 6.21 QALYs and $2054 for usual care. The incremental cost-effectiveness ratio for BT at 10 years was $29 821/QALY. At a willingness to pay per QALY of $50 000, BT continues to be cost effective unless the probability of severe asthma exacerbation drops below 0.63 exacerbation per year or the cost of BT rises above $10 384 total for all three bronchoscopic procedures needed to perform thermoplasty and to cover the entire bronchial tree (baseline = $6690). Conclusions : BT is a cost-effective treatment for asthmatics at high risk of exacerbations. Continuing to follow asthmatics treated with BT beyond 5 years will help inform longer efficacy and support its cost-effectiveness.